2020
DOI: 10.1002/ccd.29233
|View full text |Cite
|
Sign up to set email alerts
|

Adverse clinical outcomes in patients undergoing both PCI and TAVR: Analysis from a pooled multi‐center registry

Abstract: Background There is a paucity of data regarding the optimum timing of PCI in relation to TAVR. Objective We compared the major adverse cardiovascular and cerebrovascular events (MACCE) rates among patients who underwent percutaneous coronary intervention (PCI) before transcatheter aortic valve replacement (TAVR) with those who received PCI with/after TAVR. Methods In this multicenter study, we pooled all consecutive patients who underwent TAVR at three high volume centers. Results Among 3,982 patients who unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Presently, revascularization is recommended in TAVR-patients with significant CAD, however there is a lack of evidence regarding the relevance and perfect timing of PCI in these patients since studies showed conflicting results. 15,40,41 Theoretically, CTO-revascularization before TAVR may prevent periprocedural myocardial infarction during rapid pacing for valve delivery. However, the revascularization procedure of the CTO is not without risk and patients may sustain serious complications during CTO PCI before TAVR.…”
Section: Study Id Coronary Artery Disease Resultsmentioning
confidence: 99%
“…Presently, revascularization is recommended in TAVR-patients with significant CAD, however there is a lack of evidence regarding the relevance and perfect timing of PCI in these patients since studies showed conflicting results. 15,40,41 Theoretically, CTO-revascularization before TAVR may prevent periprocedural myocardial infarction during rapid pacing for valve delivery. However, the revascularization procedure of the CTO is not without risk and patients may sustain serious complications during CTO PCI before TAVR.…”
Section: Study Id Coronary Artery Disease Resultsmentioning
confidence: 99%
“…In their review, Cao et al included the timing of PCI in a flowchart of the strategy of CAD management in TAVI patients 20 . However, the recent article of Kumar et al demonstrated in a pooled multi‐center registry that the adverse events rate was similar whenever PCI was performed for patients who received TAVI 21 . There are many factors involved in this issue.…”
Section: Discussionmentioning
confidence: 99%
“… 20 However, the recent article of Kumar et al demonstrated in a pooled multi‐center registry that the adverse events rate was similar whenever PCI was performed for patients who received TAVI. 21 There are many factors involved in this issue. For example, all components of the anatomy and the severity of coronary artery stenosis and aortic valve stenosis have to be taken into consideration.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, the vast majority of patients were treated with balloon-expandable valves, which certainly imposes a limitation on results applicability. Similarly, in the US based registry in which 380 patients were treated with TAVI and PCI, the timing of PCI—either before or concomitant/after TAVI—had no impact on MACCE-free survival, and a propensity-matched analysis of 159 patients yielded similar results [ 83 , 84 ]. Yet, there was a significant discrepancy in terms of timing and number of patients, with 327 patients treated with PCI in the year before TAVI, 38 patients treated with concomitant TAVI and PCI and only 15 patients underwent PCI within two months post TAVI.…”
Section: Pci Timing In Stabile Patients With Asmentioning
confidence: 99%